PENGGUNAAN GOOGLE TRANSLATE DALAM PENERJEMAHAN TEKS BAHASA ARAB KE DALAM BAHASA INDONESIA - Faqih, Ahmad (Departemen Pendidikan Bahasa Arab, 2018)
This research was conducted to overcome the problems faced by academics on the difficulty of understanding Arabic texts with the application of Google Translate. Through qualitative descriptive methods, data obtained by interviews and questionnaires. Then data is collected which finally found various problems. Departing from these problems, the data are analyzed to find solutions to overcome them. From the results of the study found a solution, namely there need to be several steps that can be used as a guide so that the translation results are commensurate in the target language. These steps are (1) enter the whole text into the machine; (2) copy the translated text into Microsoft words; (3) read the entire equivalent in the target text; (4) compile the target text according to the structure in the target language; and (5) looking for the right equivalent in accordance with the culture contained in the source language and target language.